P31 Improving paracetamol safety in a tertiary paediatric hospital. Issue 9 (19th August 2020) - McCann, Joe; Copeland, Rachel; Keaney, Aideen; Laverty, Leanne; Marcus, Simon
Abstract : Aims: Medication errors are perhaps the most common threat to patient safety. 1 Children are particularly at risk because of variations in age and weight necessitating individual dose calculation for each patient; doses that are ten times the correct amount are occasionally given and can be life-threatening. 2 Since 2015 the hospital has been seeking, as part of a Regional Quality initiative, to improve safety related to paracetamol. Methods: Previous work involved clarification of IV paracetamol dosing for neonates and children under 10 kg with procurement of 100 mg in 10 ml vials, as well as introduction of a 'ready-reckoner' reference chart for prescribing, preparation and administration inserted into each BNFC across the hospital. In September 2018, we implemented a new prescribing aide sticker into kardexes in an effort to reduce IV administration errors. We then audited whether these interventions had led to an overall reduction in adverse incidents related to paracetamol. Results: We demonstrated a progressive reduction in adverse incidents over the past four years; it has now been more than 1000 days since the last reported serious adverse incident related to paracetamol. A snapshot audit of prescribing showed that 100% of patients were prescribed a safe dose of paracetamol by either age or weight. There was however considerable variation in dosing for enteral prescribing (8.2–18.8 mg/kg), with the majority of children (74%) being dosed according to age, despite weight being available at time of prescription. Introduction of the paracetamol prescribing aide sticker received overwhelmingly positive feedback from both medical and nursing staff, and has now been implemented for all children requiring regular IV paracetamol. Conclusions: Anaesthetics were the most commonly implicated specialty in paracetamol errors in our institution. Enteral dosing by age banding in hospital carries the potential for some children to be significantly under-dosed leading to sub-therapeutic drug levels, or even inadvertently over-dosed for more complex children who are underweight for age. We would therefore recommend dosing of enteral paracetamol by weight, when available, in hospital. Substantial improvement in paracetamol safety can be achieved through implementation of prescribing and administration aides to reduce likelihood of human error. References: Eyers S, Fingleton J, Perrin K, Beasley R. Proposed MHRA changes to UK children's paracetamol dosing recommendations: modelling study. J R Soc Med 2012;105 :263–9. Kaufmann J, Laschat M, Wappler F. Medication Errors in Paediatric Emergencies: A Systematic Analysis. Dtsch Arztebl Int 2012;109 :609–616.